Sleep disturbance, cancer-related fatigue, and depression as determinants of quality of life among breast cancer patients undergoing chemotherapy: a cross-sectional study - Abdelaziz Hendy; Rasha Kadri Ibrahim; Amani Darwish; Saher Al Sabbah; Abeer Yahia Mahdy Shalby; Rahmah Khubrani; Amal Elhaj Alawad; Sally Mohammed Farghaly Abdelaliem; Nadia Mohamed Ibrahim Wahba (BMC Cancer)
Abstract Purpose This study aims to assess effect of sleep disturbance, cancer-related fatigue, and depression on the quality of life (QoL) of breast cancer patients undergoing chemotherapy. Method A descriptive, cross-sectional study was conducted at an oncology hospital in Cairo, Egypt, from November 2024 to February 2025. A total of 253 breast cancer patients undergoing chemotherapy were recruited through convenience sampling. Data were collected using validated instruments: Pittsburgh Sleep Quality Index (PSQI), Functional Assessment of Cancer Therapy-Breast (FACT-B), Cancer Fatigue Scale (CFS), and Patient Health Questionnaire-9 (PHQ-9) for depression. Linear regression models were employed to analyze the relationships between sleep disturbance, fatigue, depression, and QoL. Results Findings revealed that 99.2% of patients experienced fatigue, 87.4% reported poor sleep, and 93.3% exhibited depressive symptoms. Regression analysis demonstrated that sleep disturbance had the strongest negative impact on QoL (B = -1.506, p < 0.001), overshadowing both fatigue and depression. Correlation analysis further supported these findings, with sleep disturbance showing the highest negative correlation with QoL (r = -0.81, p < 0.001), followed by fatigue (r = -0.72, p < 0.001) and depression (r = -0.56, p < 0.001). Conclusions Sleep disturbance, cancer-related fatigue, and depression are significantly associated with reduced QoL in breast cancer patients undergoing chemotherapy. Among these factors, sleep disturbance appears to be the most influential. Interventions targeting sleep quality may help mitigate related psychological and physical challenges, thereby enhancing patients’ overall well-being.